2019
DOI: 10.1108/mbe-09-2019-0091
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation, absorptive capacity and business performance in SMEs

Abstract: Purpose Firms must be constantly looking for markets and business opportunities and developing new products; to do so, they must find ways to increase their competitiveness, productivity so that it is noticed in their financial statements. The purpose of this paper is to establish the influence of entrepreneurial orientation (EO) in business performance (BP) of small and medium-sized enterprises of the manufacturing sector in Mexico. Likewise, it is intended to demonstrate how absorptive capacity (ACAP) allows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…On the other hand, some researchers have conducted analyses of entrepreneurial orientation, proactiveness and risk-taking [28]. They carried out their study between January 2018 to June 2018 by using two methods Structural Equation Modelling (PLS-SEM) and Fuzzy Set Qualitative Comparative Analysis (fsQCA).…”
Section: The Analysis Of Chinese-style Innovation Characteristicsmentioning
confidence: 99%
“…On the other hand, some researchers have conducted analyses of entrepreneurial orientation, proactiveness and risk-taking [28]. They carried out their study between January 2018 to June 2018 by using two methods Structural Equation Modelling (PLS-SEM) and Fuzzy Set Qualitative Comparative Analysis (fsQCA).…”
Section: The Analysis Of Chinese-style Innovation Characteristicsmentioning
confidence: 99%
“…AC takes advantage of essential resources inherent in the firm's relationships with supply chain partners and allows deploying those resources effectively to attain a sustainable competitive advantage (Gölgeci & Kuivalainen, 2020). Moreover, previous literature has confirmed that AC effectively moderates the relation between EO and other factors as performance (Engelen et al, 2014), technological innovation capabilities (Mohd Noor & Aljanabi, 2016), international performance of family firms (Hernandez-Perlines, 2018), innovation performance (Zhai et al, 2018), and business performance (Ibarra-Cisneros & Hernandez-Perlines, 2019). Therefore, the current study expands research in terms of how a firm's AC interacts with EO so as to improve SCR by arguing that AC plays a core role in boosting the effect of EO on SCR.…”
Section: Introductionmentioning
confidence: 96%
“…Entrepreneurial orientation (EO) is among the themes that have been studied widely in recent times due to its major influence on business performance (Al-Hakimi et al, 2020;Hernandez-Perlines, 2018;Ibarra-Cisneros & Hernandez-Perlines, 2019;Sarsah et al, 2020). Entrepreneurialoriented firms can respond to changes, disruptions, and environmental uncertainty by providing opportunities and allocating resources to invest for sustainment and expansion (Hisrich et al, 2016;Hitt et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that GAC had a significantly positive effect on both GEO and SEP, especially when GIP served as a mediator. This implies that successful green entrepreneurs need to absorb and explore new opportunities that suit the increasing external environmental concerns [13,112]. The GIP, which reflects a combination of GAC [111] and GEO [113], is integral to achieve the noble objective that advances industry and economy without influencing ecological systems [13,72].…”
Section: Discussionmentioning
confidence: 99%